Magnetic engineering of stable rod-shaped stem cell aggregates: circumventing the pitfall of self-bending. Issue 2 (12th January 2015) - Du, V.; Fayol, D.; Reffay, M.; Luciani, N.; Bacri, J-C.; Gay, C.; Wilhelm, C.
Abstract : During the maturation process, a rod-shaped aggregate of stem cells spontaneously bends and coils into a sphere-like structure. Abstract : A current challenge for tissue engineering while restoring the function of diseased or damaged tissue is to customize the tissue according to the target area. Scaffold-free approaches usually yield spheroid shapes with the risk of necrosis at the center due to poor nutrient and oxygen diffusion. Here, we used magnetic forces developed at the cellular scale by miniaturized magnets to create rod-shaped aggregates of stem cells that subsequently matured into a tissue-like structure. However, during the maturation process, the tissue-rods spontaneously bent and coiled into sphere-like structures, triggered by the increasing cell–cell adhesion within the initially non-homogeneous tissue. Optimisation of the intra-tissular magnetic forces successfully hindered the transition, in order to produce stable rod-shaped stem cells aggregates.